A Case Series of Metastatic Metaplastic Breast Carcinoma Treated With Anti-PD-1 Therapy - Kim, Isaac; Rajamanickam, Venkatesh; Bernard, Brady; Chun, Brie; Wu, Yaping; Martel, Maritza; Sun, Zhaoyu; Redmond, William L.; Sanchez, Katherine; Basho, Reva; McArthur, Heather; Page, David B. (Frontiers in Oncology, 2021)
Metaplastic breast cancer is a rare and often chemo-refractory subtype of breast cancer with poor prognosis and limited treatment options. Recent studies have reported overexpression of programmed death ligand 1 (PD-L1) in metaplastic breast cancers, and there are several reports of anti-PD-1/L1 being potentially active in this disease. In this case series, we present 5 patients with metastatic metaplastic breast cancer treated with anti-PD-1-based therapy at a single center, with 3 of 5 cases demonstrating a response to therapy, and one of the responding cases being a metaplastic lobular carcinoma with low-level hormone receptor expression. Cases were evaluated for PD-L1 expression, tumor infiltrating lymphocytes (TILs), DNA mutations, RNA sequencing, and T-cell receptor sequencing. Duration of the response in these cases was limited, in contrast to the more durable responses noted in other recently published reports.